2018
DOI: 10.1111/jocn.14242
|View full text |Cite
|
Sign up to set email alerts
|

Child healthcare nurses’ experiences of asking new mothers about intimate partner violence

Abstract: The Violence in Families questionnaire was regarded as a useful tool and could thus be implemented in practice. However, it is important to offer education to the nurses prior to implementing a routine of asking about intimate partner violence in the child healthcare setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…The findings from this study substantiate earlier work which identifies training and education as a key enabler in both initiating and sustaining family violence enquiry 5. The short questionnaire ViF used in this study2 was found to be a valuable tool to engage the mothers in a conversation about IPV. However, it is important to ensure that using a prescribed short tool does not then turn into a mere tick-box exercise.…”
Section: Commentarysupporting
confidence: 85%
See 1 more Smart Citation
“…The findings from this study substantiate earlier work which identifies training and education as a key enabler in both initiating and sustaining family violence enquiry 5. The short questionnaire ViF used in this study2 was found to be a valuable tool to engage the mothers in a conversation about IPV. However, it is important to ensure that using a prescribed short tool does not then turn into a mere tick-box exercise.…”
Section: Commentarysupporting
confidence: 85%
“…A quasi-experimental design was employed at 12 child healthcare centres in Sweden in 2015 2. The project was a small-scale intervention using a two-step approach for talking about IPV with mothers.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying IPV survivors in clinical practice may help them connect with needed support and safety services, thereby potentially reducing exposures to violence (Ali & McGarry, 2018;Anderzen-Carlsson et al, 2018;Ferranti et al, 2018). However, research has consistently demonstrated many frontline healthcare providers are uncomfortable in screening and counselling patients for IPV (Alvarez et al, 2017(Alvarez et al, , 2018Rees et al, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Therefore, it is not enough just to recognize them, it is necessary to train professionals so that they can offer safe care in a welcoming environment, providing security so that victims have the opportunity to talk about it without any fear and fear. 19 Although nursing science respects human rights and acts to minimize the individual's biopsychosocial suffering, failures in the care of this population are still evident, which indicates lack of knowledge and training regarding the referral, identification and compulsory notification of cases of violence. The nursing staff must adopt welcoming, safe and private behaviors so that this scenario can be modified.…”
Section: Education As a Tool To Minimize Workplace Violencementioning
confidence: 99%
“…20 Therefore, Health Education and PE are important during health promotion activities in situations of violence, favoring possibilities for effective nursing practice, expanding concepts, competencies and skills of professionals, as well as of the assisted population. 19 It is necessary for professionals to be aware that there are educational and managerial strategies that help them in making decisions and changes related to care and approach, so that they collectively and individually favor them in relation to eventual cases involving violence in the workplace perpetrated by the patients themselves, as well as their families and co-workers.…”
Section: Education As a Tool To Minimize Workplace Violencementioning
confidence: 99%